Pengaruh Jual Beli Online E-Commerce Shopee Terhadap Minat Beli Saat Pandemi Covid-19 Pada Masyarakat Milenial Di Kecamatan Belitang - Aceria Mega Putri Pratiwi; Ambok Pangiuk; Muhammad Ismail (Journal of Management and Creative Business, 2023)
This study aims to find out how much influence online buying interest has on the Shopee marketplace among millennial communities during the Covid-19 Pandemic. This study uses quantitative research, data collection in this study using a questionnaire which uses a simple random sampling technique where population data collection is done randomly. The sample of this study was 100 respondents who were taken from the millennial generation of Generation Z. This study was conducted to examine the effect of buying and selling online on buying interest during the Covid-19 pandemic in millennial society. The results of the study stated that buying and selling online on buying interest. Based on the t-test there is an influence between buying and selling online on buying interest received. There is a positive and significant influence on the online buying and selling variable on buying interest (case study of shopee online shop).